DNA methylation change of HIPK3 in Chinese rheumatoid arthritis and its effect on inflammation - Jiang, Ping; Wei, Kai; Xu, Lingxia; Chang, Cen; Zhang, Runrun; Zhao, Jianan; Jin, Yehua; Xu, Linshuai; Shi, Yiming; Qian, Yi; Sun, Songtao; Guo, Shicheng; et al. (Frontiers in Immunology, 2023)
Homeodomain-interacting protein kinase 3 (HIPK3) play an important role in cell proliferation, apoptosis and inflammation. Over-expression of HIPK3 in immune cell in rheumatoid arthritis (RA) has been identified. In this study, we investigate blood methylation level with clinical characteristics of RA . 235 RA patients, 30 OA patients and 30 matched healthy controls were recruited . Methylation status of 7 CpGs in the differentially methylated region of HIPK3 (cg05501357) were measured by targeted methylation sequencing technology. Association between methylation haplotypes and overall methylation status of HIPK3 with clinical characteristics was performed with generalized linear regression. We found all 7 CpGs showed hypomethylation status in RA blood compared with OA and normal individuals with overall P=1.143×10-8 and FDR=2.799×10-7, which is consistent with previously reported high expression HIPK3 in RA immune cells. Among all 7 CpGs, the 33286785 shows highest predictive power with AUC=0.829, What’s more, we can receive a higher AUC=0.864 when we combined HIPK3 with ACPA (-) and RF (+) in the prediction model, it shows that when the patient's ACPA is negative, HIPK3 can assist RF as a new clinical index for the diagnosis of RA. We also found the HIPK3 methylation levels is negative correlated with C-reactive protein (CRP) (r=-0.16, p=0.01). Methylation haplotypes are analyzed and found full methylation haplotype (FMH) (r=0.16, p=0.01) and full non-methylation haplotype (FNH) (r=0.18, p=0.0061) also negatively correlated with CRP. Circulating blood methylation level of protein region of HIPK3 can be utilized as supportive diagnostic biomarker and CRP level indicator for RA.